It is 7 times 6 = 42
-6d = -42-6(7) = -42d = 7
6 times -7 = -42
Well, honey, if you want to know what divided by 7 equals 6, the answer is 42. That's right, 42 divided by 7 gives you 6. So, there you have it, simple math for a simple question.
42
6 times -7 is -42
It is 7 times 6 = 42
42, because if there is nothing between the 7 and 'a' and 'a' equals 6 then the answer is 42.
first do 42 divided by 7, which equals 6. 1/7 of 42=6
6
7 times 6 equals 42 :)
-6d = -42-6(7) = -42d = 7
6 times -7 = -42
Well, honey, if you want to know what divided by 7 equals 6, the answer is 42. That's right, 42 divided by 7 gives you 6. So, there you have it, simple math for a simple question.
42
42
It is a nonsensical statement.